Pseudo-Decentralization: Contesting the Top-Down and Bottom-Up National Free Nutritional Meal Programs - Akbar A; Nayzilah Dea Ristyani Hasbi; Velly V; Lauria Desinta Indri; Andini Ayu Okviani; Fajrina Nurasya (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Decentralization is a fundamental principle in Indonesia’s system of governance, aimed at strengthening the role of local governments in planning and public service delivery. However, in practice, nationally scaled social policies often demonstrate the dominance of a top-down approach. This article seeks to analyze the characteristics of top-down and bottom-up approaches in the planning of the Free Nutritious Meal Program and to identify the potential occurrence of pseudo-decentralization in its policy design. This study employs a qualitative approach using a literature review method, drawing on various academic sources and policy documents relevant to decentralization, development planning, social policy, and food security within the framework of the Sustainable Development Goals formulated by the United Nations. The findings indicate that the program design is predominantly characterized by a top-down approach through national standardization and centralized budget control. Although this ensures policy consistency, such dominance may limit local adaptability and generate indications of pseudo-decentralization. In the context of achieving SDG 2, SDG 3, and SDG 4, the program’s effectiveness is largely determined by the synergy between central strategic direction and local implementation capacity. Therefore, a more balanced integration of top-down and bottom-up approaches is a crucial prerequisite for supporting sustainable development.